2021
DOI: 10.3390/jcm10081621
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Decline of Serum Proprotein Convertase Subtilisin/Kexin 9 (PCSK9) in Non-Cirrhotic Patients with Chronic Hepatitis C Infection Receiving Direct-Acting Antiviral Therapy

Abstract: Direct-acting antivirals (DAAs) efficiently eradicate the hepatitis C virus (HCV). Low-density lipoprotein (LDL) levels increase rapidly upon DAA treatment. Proprotein convertase subtilisin/kexin 9 (PCSK9) induces degradation of the hepatic LDL receptor and thereby elevates serum LDL. The aim of this study was to determine serum PCSK9 concentrations during and after DAA therapy to identify associations with LDL levels. Serum PCSK9 was increased in 82 chronic HCV-infected patients compared to 55 patients not in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 59 publications
(62 reference statements)
2
25
0
Order By: Relevance
“…Most studies used commercially available ELISAs to determine systemic PCSK9 levels, and could not discriminate between the active and less active isoforms. In contrast to the abovementioned report, total serum PCSK9 concentrations declined 4 weeks after therapy initiation and remained low up to 12 weeks post-treatment [129]. Reduced circulating PCSK9 levels were also detected in a cohort of 48 HCV-infected patients after successful DAA therapy [126] (Figure 2), while posttreatment plasma PCSK9 concentrations were induced in 27 HCV patients who achieved sustained virologic response [121].…”
Section: Pcsk9 and Hcv-induced Chronic Liver Diseasementioning
confidence: 71%
See 4 more Smart Citations
“…Most studies used commercially available ELISAs to determine systemic PCSK9 levels, and could not discriminate between the active and less active isoforms. In contrast to the abovementioned report, total serum PCSK9 concentrations declined 4 weeks after therapy initiation and remained low up to 12 weeks post-treatment [129]. Reduced circulating PCSK9 levels were also detected in a cohort of 48 HCV-infected patients after successful DAA therapy [126] (Figure 2), while posttreatment plasma PCSK9 concentrations were induced in 27 HCV patients who achieved sustained virologic response [121].…”
Section: Pcsk9 and Hcv-induced Chronic Liver Diseasementioning
confidence: 71%
“…These findings implied HCV genotypedependent effects on plasma PCSK9 levels, but while other studies confirmed HCV-induced PCSK9 serum levels, a link to HCV genotypes was not described [126][127][128][129]. HCV infection also elevated serum PCSK9 levels in noncirrhosis and cirrhosis patients as well as HIVinfected patients [129,130]. On the other hand, LDL levels did not correlate with plasma PCSK9 concentrations in chronic HCV [125,127,129].…”
Section: Pcsk9 and Hcv-induced Chronic Liver Diseasementioning
confidence: 74%
See 3 more Smart Citations